Evaluation of ash melting behavior in pulverized coal-fired furnace from proportion of amorphous phase in fly ash. (1st December 2019) - Matsui, Yohei; Wakabayashi, Nobuyuki
Highlights: Ash melting causes generation of high-strength clinkers. Amorphous phase in coal ash cooled rapidly represents ash melting behavior. Ash melting behavior in actual conditions can be estimated by a brief analysis. Abstract: Molten ash in pulverized coal-fired boilers has significant effects on the generation of high-strength clinkers, which cause issues in boiler operations. To predict ash melting behavior in actual utility boilers is difficult because the melting behavior is influenced by various factors such as ash chemical composition, temperature, gas composition, etc. In this study, coal combustion and ash deposition experiments were conducted in a 760 kW coal combustion furnace to develop a method for investigating the ash melting behavior. Additionally, the proportion of the amorphous phase in the fly ash obtained from a bag filter was investigated by the Rietveld quantitative analysis of X-ray diffraction data. As a result, the proportion of the amorphous phase in the fly ash was high when high-strength clinkers with molten surfaces were generated. The results indicated that most of the molten phase in the fly ash particles transformed into the amorphous phase because they were cooled rapidly by being transported into the bag filter, resulting in the inhibition of their crystallization. Hence, we concluded that the proportion of the amorphous phase in the fly ash captured by cold ash collectors represents the ash melting behavior in the actual environments. The proposed method can be used to evaluate the effects of fuel or boiler-operating conditions on ash melting behavior. The applications of the method on actual utility boilers will be considered in further studies.